Rounding-augmented reality book and smartphone for deaf students in achieving basic competence. (April 2020) - Hasanah, A; Kusumah, Y S; Rahmi, K
Abstract: Deaf students' hearing problem results in their mastery of language and mathematics lower than hearing students. Learning the topic of rounding is difficult for deaf students because it requires a good understanding of language and a true perception in math concepts, in which are abstract in nature. Learning concepts needs a special strategy for this type of students, as generally mathematics is difficult to be translated and communicated by sign language. This specificity forces them to possess unique behavior in understanding everything through visual power. This paper discusses a study of the creation of a book and smartphone applications as devices based on augmented-reality (AR) software on the topic of rounding accompanied by rich visualization to facilitate deaf students in achieving mathematical basic competencies. This study aims to describe and reveal the validity and the effectiveness of the designed devices through their implementation in a classroom. The research and development method refer to ADDIE which consisting of five stages, namely: analysis, design, development, implementation, and evaluation. The results of this study show that the AR-Book and the AR-Smartphone application are valid used by deaf students and both devices are effective in achieving their mathematical basic competencies.